2019
DOI: 10.3390/microorganisms7030089
|View full text |Cite
|
Sign up to set email alerts
|

Field Based Assessment of Capsicum annuum Performance with Inoculation of Rhizobacterial Consortia

Abstract: Plant growth promoting rhizobacteria (PGPR) are associated with plant roots and augment plant productivity and immunity by reducing fertilizer application rates and nutrient runoff. Studies were conducted to evaluate bell pepper transplants amended with formulation of consortium of two indigenous PGPR isolates (Bacillus subtilis and Bacillus pumilus) in terms of increase in yield and disease resistance under field conditions. Transplants were planted into plots treated by NPK (nitrogen, phosphorus and potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Bio-stimulant could be applied in different methods including seed soaking and plat drenching. The study found that vegetative growth, crop yield and crops resistance against plant diseases (damping off and anthracnose) increased when chili seeds were soaked for 30 minutes in 1 mL of bio-stimulant (microbial consortium) and 10 mL of bio-stimulant was applied to the plant at the time of flowering [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bio-stimulant could be applied in different methods including seed soaking and plat drenching. The study found that vegetative growth, crop yield and crops resistance against plant diseases (damping off and anthracnose) increased when chili seeds were soaked for 30 minutes in 1 mL of bio-stimulant (microbial consortium) and 10 mL of bio-stimulant was applied to the plant at the time of flowering [16].…”
Section: Resultsmentioning
confidence: 99%
“…The use of seaweed to stimulate plant growth has been implemented in various crops, for instance okra [7], Tagetes [8], chickpeas [9], [10], and chili [11]. Additionally, beneficial bacteria have been widely used as bio-stimulants in various plants, including lettuce [12], rice, corn [13], strawberry [14], rice [15], and chili [16]. While beneficial fungi have been applied to rice [17] and chili [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of rhizobacteria and rhizobium improves mungbean overall growth as compared to their single inoculation with rhizobium ( Kumari et al, 2020 ). A consortium of two PGPR isolates ( Bacillus subtilis and Bacillus pumilus ) was used by the consortium to increase the yield of the bell pepper plant and disease resistance under field conditions ( Kaushal et al, 2019 ). Two PGPR strains ( Acinetobacter sp .…”
Section: Application Of Natural Rhizobacterial Consortium and Enginee...mentioning
confidence: 99%
“…Many studies related to the use of one type of seaweed bio-stimulant have been carried out, including on chickpeas [18,19], dates [20], tomato seedlings [21], leeks [22], chili [23,24], and few reported the use of seaweed [25] on shallot plants. The use of beneficial bacteria as bio-stimulants in various plants has also been carried out, including in lettuce [26], rice and corn [27], strawberries [28], rice [29], maize [30,31], potatoes [32], soybean [33], kailan [34], chili [35,36] etc. Several studies are known to use beneficial bacteria to increase the growth of shallots [37,38,39,40].…”
Section: Introductionmentioning
confidence: 99%